Short‐Term Changes in Physical and Chemical Properties of Soil Charcoal Support Enhanced Landscape Mobility. Issue 11 (29th November 2017) - Pyle, Lacey A.; Magee, Kate L.; Gallagher, Morgan E.; Hockaday, William C.; Masiello, Caroline A.
Abstract: Charcoal is a major component of the stable soil organic carbon reservoir, and the physical and chemical properties of charcoal can sometimes significantly alter bulk soil properties (e.g., by increasing soil water holding capacity). However, our understanding of the residence time of soil charcoal remains uncertain, with old measured soil charcoal ages in apparent conflict with relatively short modeled and measured residence times. These discrepancies may exist because the fate of charcoal on the landscape is a function not just of its resistance to biological decomposition but also its physical mobility. Mobility may be important in controlling charcoal landscape residence time and may artificially inflate estimates of its degradability, but few studies have examined charcoal vulnerability to physical redistribution. Charcoal landscape redistribution is likely higher than other organic carbon fractions owing to charcoal's low bulk density, typically less than 1.0 g/cm 3 . Here we examine both the physical and chemical properties of soil and charcoal over a period of two years following a 2011 wildfire in Texas. We find little change in properties with time; however, we find evidence of enhanced mobility of charcoal relative to other forms of soil organic matter. These data add to a growing body of evidence that charcoal is preferentially eroded, offering another explanation for variations observed in its environmental residence times. Key Points: Variability in postfire SOM composition is driven by fire heterogeneity for most SOM forms Charcoal spatial heterogeneity is additionally driven by preferential redistribution Subtropical forest wildfire charcoal has a porosity of 69.7% ± 12. 6%. Soil aging over short timescales does not impact charcoal porosity